A focus on ethical value under the vision of leadership, teamwork, effective communication and productivity - Víctor Mercader; Esthela Galván-Vela; Rafael Ravina Ripoll; Cristina Raluca Popescu (Journal of Risk and Financial Management, 2021)
The new economy and the knowledge-based society brought significant changes in all the areas of our daily lives. Also, the COVID-19 pandemic and the COVID-19 crisis implicated tremendous transformations in all the domains, on the one hand, threatening the balance of our society and, on the other hand, challenging the dynamic of the new economy development and the rhythm of the societal modernization. In these delicate times, the all-important relationship between ethics, leadership, teamwork, effective communication, productivity, and performance is brought to the attention, in particular, due to its benefits for our society, taking into consideration the pivotal advancement that a well governed relationship of this type could provide to the knowledge-based economy. The present research describes the implication of ethics in leadership, teamwork, effective communication, and productivity, which includes the application of ethical values as university graduates assume the role of each of the mentioned dimensions of study in the organizations. The absence of research that relates ethics to these four elements simultaneously was noticed. This information is essential to know how these dimensions influence the organizational level. The sample that included 410 university graduates was applied in Baja California, Mexico, and the industrial nucleus of great relevance, bordering California in the United States of America. The data was obtained using a questionnaire. A reliability and validity analysis of the measurement instrument was carried out in terms of the ethical values associated with the dimensions mentioned using the exploratory factor analysis by the principal components method. Qualitative items were also analyzed using the constant comparison method. The results obtained in this research provide a greater perspective and practical knowledge and support of usefulness and practical reality to businesspeople and employees, leaders and university graduates; and also extensive to students, teachers, and human beings in general, in order to be better prepared to give and apply solutions with their consequent ethical and productive achievements desired by all. Additionally, this current research has the purpose to raise the will to understand, at a higher level and at a more in-depth degree of knowledge, the relationship between ethics, leadership, teamwork, effective communication, productivity, and performance, in the attempt to foster a creative and innovative business environment, based on a robust and sustainable business administration and business competencies, capable to position at higher ranks the strengths, opportunities, aspirations and outcomes that today's new economy is due to offer and diminish the dangerous effects of the COVID-19 pandemic and the COVID-19 crisis in all the domains.
Keywords: 330; ethics; leadership; teamwork; effective communication; productivity; performance; business administration; business environments; business competencies; business counseling; corporate governance; creativity; economics; effective business communication; effectiveness; entrepreneurial competencies; entrepreneurship; environmental protection; knowledge-based society; innovative business models; integrative strategies; intellectual capital; accounting; audit; economic and financial analysis; economic growth; fiscally responsible businesses; intangible assets; human capital; human resources management; management; mindfulness; qualitative analysis; quantitative analysis; questionnaire; performance management; public sector; private sector; statistics; statistical correlations; study sample; Sustainable Development Goals (SDGs); sustainability; empirical analysis; exploratory analysis; exploratory factors; Barlett’ s sphericity test; Cronbach’ s alpha indicator; Kaiser-Meyer Olkin (KMO) test; Likert scale; skewness and kurtosis calculations; Varimax rotation; voluntarist theory; COVID-19 pandemic